Embracing Christian Values: Positive Relationships and Academic Achievement in Higher Education - Fowler, David; Musgrave, Jon (Universitas Pelita Harapan, 2024)
This literature review and analysis intricately examines the dynamic interplay between educators and students within the realm of higher education, with a keen focus on the spiritual dimensions elucidated by Christian principles and biblical wisdom. Rooted in the fundamental belief that education embodies a sacred journey, this study delves deep into the profound impact of positive relationships on both academic achievements and spiritual maturation. By establishing meaningful connections between contemporary educational practices and timeless biblical teachings, the research sheds light on how Christian virtues, such as love, compassion, and empathy, serve as foundational pillars in cultivating a spiritually enriching learning environment. The synthesis of empirical studies, theoretical frameworks, and biblical insights not only enhances our understanding of the transformative potential of positive relationships in higher education but also underscores their pivotal role in fostering holistic development on a spiritual level. Through this comprehensive exploration, the study contributes significantly to the discourse on the symbiotic relationship between academic success and spiritual growth, emphasizing the importance of nurturing positive relationships as a cornerstone of holistic education in higher learning institutions.